Bentuk Pemberdayaan UMKM Dalam Melakukan Pendampingan di Rumah BUMN Semarang - Asfarina Adha Rahmayanti; Alistya Putri; Meddiati Fajri Putri; Denny Yuda Kurniawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
MSME empowerment requires mentoring that goes beyond short-term training and should be directed toward sustainable business capacity building. This article aims to describe the forms of MSME empowerment implemented through mentoring activities at Rumah BUMN Semarang. The implementation method combines community education, training, consultation, and advocacy through needs identification, material preparation, mentoring implementation, hands-on practice, and output evaluation. The target participants are MSME actors assisted by Rumah BUMN Semarang who require capacity strengthening in business legality, business management, product branding, digital marketing, simple financial recording, and market networking. The results show that relevant empowerment forms include business problem mapping, thematic training, business clinics, digital practice assistance, legality facilitation, and collaborative network strengthening. The mentoring activities also encourage MSME actors to manage product identity, create promotional content, use digital channels, and prepare business development plans. This activity concludes that Rumah BUMN Semarang can function as an incubation space that strengthens MSME independence and competitiveness through structured, participatory, and continuous mentoring.